Dissection of Individual Prostate Lobes in Mouse Models of Prostate Cancer to Obtain High Quality RNA. Issue 1 (1st April 2016) - Zingiryan, Areg; Farina, Nicholas H.; Finstad, Kristiaan H.; Stein, Janet L.; Lian, Jane B.; Stein, Gary S.
Abstract : Genetically engineered mouse models of prostate cancer allow for study of disease progression from localized tumor formation through distal metastasis. The anatomy of the mouse prostate differs dramatically from the human prostate, being composed of four lobe pairs (anterior, dorsal, lateral, and ventral), making the identification and dissection technically challenging. Although the entire murine prostate and surrounding tissue, including urethra, bladder, seminal vesicles, and associated adipose tissue, can be quickly dissected for en bloc analysis, it is necessary to isolate individual prostate lobes for gene expression studies elucidating the molecular mechanisms of prostate cancer. The procedure as described here includes full color images, allowing the researcher to appreciate the unique prostate morphology and tissue manipulation required to harvest individual prostate lobes. Along with removing all extraneous tissue, the procedure allows for direct comparison of the different prostate lobes by established downstream techniques. Importantly, high quality RNA required for next‐generation gene expression analysis can only consistently be obtained from ventral and lateral lobes. Finally, preclinical studies using prostate targeted therapies can be monitored specifically in individual prostate lobes for histological and gene expression studies. J. Cell. Physiol. 232: 14–18, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Here, we present a procedure with full color images to isolate individual murine prostate lobes, free of adjacent tissue, for use in downstream gene expression studies. All eight murine prostate lobes can be harvested within an hour and processed for histologic analysis and molecular component isolation (RNA, DNA, protein, etc.). Only the lateral and ventral prostate lobes yield non‐degraded RNA.